2014
DOI: 10.1080/17470218.2013.836235
|View full text |Cite
|
Sign up to set email alerts
|

Reactive and Proactive Control Adjustments under Increased Depressive Symptoms: Insights from the Classic and Emotional-Face Stroop Task

Abstract: The current research investigated differences in reactive and proactive cognitive control as a function of depressive symptomatology. Three participant groups with varying symptom levels (Beck Depression Inventory–II, BDI–II score) completed both the classic and an emotional-face Stroop task separately under speed and accuracy instructions. All groups made equivalent speed–accuracy trade-offs independent of task, suggesting that proactive adjustments are unaffected by depressive symptoms. Additionally, groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 74 publications
1
23
0
Order By: Relevance
“…The failure for participants with depression symptoms to engage cognitive control following errors on emotional stimuli builds upon previous work, reviewed above, that indicates a cognitive control impairment in depression when emotional regulation is required (Holmes & Pizzagalli, ; Saunders & Jentzsch, ). It is also consistent with several other lines of research that describe an association between error detection and correction, and emotional regulation.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…The failure for participants with depression symptoms to engage cognitive control following errors on emotional stimuli builds upon previous work, reviewed above, that indicates a cognitive control impairment in depression when emotional regulation is required (Holmes & Pizzagalli, ; Saunders & Jentzsch, ). It is also consistent with several other lines of research that describe an association between error detection and correction, and emotional regulation.…”
Section: Discussionmentioning
confidence: 62%
“…Compared to subjects with low depression scores, those with elevated depression showed faster RT (accompanied by a lower accuracy) following errors. Similarly, Saunders and Jentzsch () found subjects with high depression scores had disrupted reactive control mechanisms, as evidenced by an impaired congruency sequence effect, in an emotional Stroop task, but not in a classic Stroop task. Importantly, the emotional Stroop task requires emotional regulation, whereas the classic Stroop task does not.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, recent studies demonstrated that if conflicts are mediated by emotional categories, different neural systems and different control processes are involved (Egner, Etkin, Gale, & Hirsch, 2008;Etkin, Egner, Peraza, Kandel, & Hirsch, 2006;Etkin, Egner, & Kalisch, 2011;Maier & di Pellegrino, 2012;Mohanty et al, 2007;Monti, Weintraub, & Egner, 2010;Saunders & Jentzsch, 2013;. When participants had to discriminate between fearful and happy faces while ignoring congruent or incongruent emotional words ("anxious", "happy"), high response conflict led to decreased activity in the amygdala on the subsequent trial (Egner et al, 2008;Etkin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%